Prospective School Counselors’ Perspectives On Remote Counseling Using Postmodern Paradigm - Purwaningrum, Ribut; Suryawati, Citra Tectona; Almubarokah, Qothrunnad (Universitas Ahmad Dahlan, 2023)
This case study was conducted with the phenomenon that in the School Field Introduction (PLP) activities, many prospective BK teachers practice distance counseling using a postmodern approach. Distance counseling is a counseling strategy that needs to be mastered by all prospective BK teachers. This is based on the growing needs of the community, including the school community, for mental health services and distance counseling services. This study involved 10 prospective BK teachers as the main subjects selected using purposive sampling, with a data collection tool in the form of an in-depth interview guide instrument. The research method is a qualitative research method with a case study design. The objectives of this study are to: a) describe how theoretical understanding of prospective BK teachers about counseling with a postmodern approach is carried out in a distance mode?, b) describe how prospective BK teachers' perspectives on the implementation of distance counseling practices with a postmodern approach that they do?, c) describe how effective the implementation of distance counseling with a postmodern approach is based on the practices that have been carried out by prospective BK teachers. The results of in-depth interviews explain that prospective BK teachers already have adequate theoretical understanding even though in practice there are still many shortcomings; the implementation of distance counseling is needed today because it is needed by the community and is efficient when carried out; and long-distance counseling with a postmodern approach can be carried out effectively if the prerequisites of facility readiness, counselor readiness, and client readiness are met. Further research can be designed to improve the skills of prospective BK teachers in organizing long-distance counseling with a postmodern approach. Further researchers can also conduct experimental research or promotion on prospective users.